Institutional Innovation and the Adoption of New Technologies : The Case of Steam - Berger, Thor; Ostermeyer, Vinzent (Journal of Economic History, 2025)
This paper documents how the advent of the limited liability corporation contributed to the diffusion of steam technology during Sweden's industrialization. Using longitudinal establishment-level data, we show that incorporation sharply raised the probability that industrial establishments adopted steam. Incorporation facilitated technology adoption partly by enabling smaller establishments to expand to a greater scale, where the use of steam became feasible. These results highlight that low barriers to incorporation may be an important lever for facilitating the diffusion of new technologies.